Regional Differences in Support for Secession Among Members of the Igbo Ethnic Group in Nigeria - Daniel Tuki (Nationalism and Ethnic Politics, 2025)
Although members of the Igbo ethnic group generally express strong support for the secession of Nigeria's Eastern Region to establish the Republic of Biafra, there is a noticeable gap in studies examining whether Igbos living in the Eastern Region (i.e., the proposed territory of Biafra) exhibit greater support for secession than those living outside of it. This study uses regression analysis to examine data from Rounds 7 and 9 of the Afrobarometer survey, revealing that individuals residing in the Eastern Region indeed express significantly stronger support for secession than those living outside of it. This heightened support might be because residents of Eastern Nigeria rely on the region for their livelihoods, making them less inclined to support a united Nigeria. Furthermore, they may lack robust social connections with people from other ethnic groups outside of the Eastern Region. Consistent with this explanation, regression analysis also shows that Igbos living in the Eastern Region are more hesitant than those living outside of it to have people from different ethnic groups as neighbors.
https://doi.org/10.7910/DVN/MRJDGH
Keywords: 330